The Wage Premium from Foreign Language Skills - Jacek Liwiński (Global Labor Organization (GLO), 2018)
The globalization of labour markets makes language skills one of the key competences required by employers nowadays. Our purpose is to estimate the wage premium from foreign language skills (FLS) earned by the Poles. We also want to find out whether this premium is affected by the fact of working in Poland or abroad. The Poles seem to be a good case study, because the Polish language is not used for international communication, while as much as 58% of Poles command at least one foreign language and 5% of Poles earn their income abroad. We use data from three waves (2012-2014) of the Human Capital Balance survey with a pooled sample of about 35,000 individuals. We estimate wage equation with the Heckman correction for selection to employment and we check for robustness with propensity score matching. We find that the advanced command of a foreign language bring a 6% wage premium to individuals working in Poland and 22% to those working abroad. Interestingly, those working in Poland earn a much higher wage premium from proficiency in Spanish (29%), Italian (20%) or French (19%) than from proficiency in English (8%). But the English language is the only foreign language that brings a wage premium to Poles working abroad.
Keywords: I26; J24; 330; foreign language skills; wage premium; wage equation